Analysis of β-amylase gene (Amyβ) variation reveals allele association with low enzyme activity and increased firmness in cooked sweetpotato (Ipomoea batatas) from East Africa - Banda, L.; Kyallo, Martina M.; Domelevo Entfellner, Jean-Baka; Moyo, M.; Swanckaert, J.; Mwanga, Robert O.M.; Onyango, A.; Magiri, E.; Gemenet, Dorcus C.; Yao, N.; Pelle, Roger; Muzhingi, T. (Elsevier, 2021)
β-amylase is a thermostable enzyme that hydrolyses starch during cooking of sweetpotato (Ipomoea batatas) storage roots, thereby influencing eating quality. Its activity is known to vary amongst genotypes but the genetic diversity of the beta-amylase gene (Amyβ) is not well studied. Amyβ has a highly conserved region between exon V and VI, forming part of the enzyme's active site. To determine the gene diversity, a 2.3 kb fragment, including the conserved region of the Amyβ gene was sequenced from 25 sweetpotato genotypes. The effect of sequence variation on gene expression, enzyme activity, and firmness in cooked roots was determined. Six genotypes carrying several SNPs within exon V, linked with an AT or ATGATA insertion in intron V were unique and clustered together. The genotypes also shared an A336E substitution in the amino acid sequence, eight residues upstream of a substrate-binding Thr344. The genotypes carrying this allele exhibited low gene expression and low enzyme activity. Enzyme activity was negatively correlated with firmness (R = −0.42) in cooked roots. This is the first report of such an allele, associated with low enzyme activity. These results suggest that genetic variation within the AmyB locus can be utilized to develop markers for firmness in sweetpotato breeding.